La integración sociopolítica de los jóvenes en tiempos inciertos - Benedicto, Jorge (SocietàMutamentoPolitica, 2015)
The structural transformations experienced by western societies in last decades and the hegemony of neoliberal policies have modified the patterns of social reproduction which guaranteed the youth social integration in adulthood. The most evident consequence of this new context is the breakdown of intergenerational contract that organized the coexistence and legitimacy of European democracies in the phase of welfare capitalism. The effects of this “unfulfilled promise” of integration, now emphasized by big crisis, are experienced with frustration and uncertainty for many young people, forcing them to seek new ways of integration. This article analyses the characteristics of youth integration in the global capitalism, the meanings young people attribute to it and the strategies that they develop to survive in “unsettled times”.